Whole-Body Vibration Exercise on Hematology and Serum Biochemistry in Healthy Dogs - Charas Santos, Ivan Felismino [UNESP]; Rahal, Sheila Canevese [UNESP]; Shimono, Jussara [UNESP]; Tsunemi, Miriam [UNESP]; Takahira, Regina [UNESP]; Teixeira, Carlos Roberto [UNESP] (Elsevier B.V., 2017)
The present study aimed to evaluate the influence of whole-body vibration (WBV) exercise on hematology and serum biochemistry in healthy dogs. Ten intact beagle dogs, 3 females, and 7 males, with a mean age of 3 years, and mean body mass of 14.3 kg, body condition score between 4.0/9 and 4.5/ 9 were evaluated. The WBV sessions were done with the dog standing up on all 4 feet on a vibrating platform. Daily session of 30 Hz for 5 minutes, followed by 50 Hz for 5 minutes and finishing with 30 Hz for 5 minutes was accomplished for 5 days. The velocity and amplitude of the vibrating platform were 12-40 m/s(2) and 1.7-2.5 mm, respectively. Blood samples were collected, before and immediately after the WBV platform exercise session, and 1 and 6 hours after the end of each session for 5 days. In addition, blood samples were collected 24 hours and 48 hours after the last WBV platform exercise session. Complete blood count and serum biochemistry (alanine aminotransferase, aspartate aminotransferase, creatine kinase, blood urea nitrogen, creatinine, and serum total protein) were the data analyzed. The erythrocytes, hemoglobin, and packet cell volume values decreased, whereas the leukocytes, neutrophils, and eosinophils values increased after WBV platform exercise sessions; however, all values were within the reference range. Other hematological and serum biochemical parameters did not show important variations. In conclusion, the WBV exercise sessions attended for 5 consecutive days did not adversely affect the hematology and serum biochemistry of adult healthy dogs. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: training; animal; blood profile; vibration